Acupoint massage combined with Traditional Chinese Medicine soaking therapy and nursing of a patient with hand-foot syndrome caused by oral administration of capecitabine for colorectal cancer (穴位按摩联合中药泡洗疗法治疗1例肠癌患者口服卡培他滨致手足综合征的护理) - LI Xiaomin (李晓敏); LIU Shuhong (刘书红) (中西医结合护理)
This paper investigate the effect of acupoint massage combined with Traditional Chinese Medicine soaking therapy in the treatment of hand-foot syndrome caused by oral administration of capecitabine in a patient with colorectal cancer, and summarized related nursing measures. A set of interventions including reduced or discontinued chemotherapy drugs, oral administration of vitamin B6 tablets, cyclooxygenase-2 (COX-2) inhibitors, and local use of hormone ointments failed to alleviate hand-foot syndrome. Individualized nursing plan was performed for the patient: Traditional Chinese Medicine soaking therapy and massage on acupoints of the large intestine meridian of the hand Yangming meridian and other local acupoints were carried out to relieve the symptoms of hand-foot syndrome. Symptoms of hand-foot syndrome were effectively relieved after treatment. The acupoint massage combined with Traditional Chinese Medicine soaking therapy is effective in alleviating hand-foot syndrome and reduce the adverse drugs reaction of oral administration of capecitabine, and contributes to the clinical treatment and improve of quality of life of the patient with colorectal cancer. (本文观察穴位按摩联合中药泡洗疗法治疗1例肠癌患者口服卡培他滨致手足综合征的效果, 总结护理经验。在应用一系列减量或停止化疗药物、口服维生素B6片、环氧合酶 2(COX-2)抑制剂、局部使用激素软膏等治疗方法后, 患者手足综合征未缓解。为患者制定个体化护理方案, 选择患者手阳明经大肠经穴位及其他局部穴位进行穴位按摩, 同时联合中药泡洗。治疗后患者双手温度恢复正常, 双手指脱屑缓解, 麻木伴刺痛感消失, 色素沉着轻微改变。采用穴位按摩联合中药泡洗疗法, 能够有效缓解手足综合征的症状, 减轻不良反应严重程度, 对确保临床治疗及护理效果、提升患者生活质量具有积极意义。)